Plan de negocios para la creación de un centro recreativo integral y pista de madera para patinaje, en la ciudad de Quevedo, año 2013 - Arevalo Roque, Diana Carolina (2013)
The business activity is to provide a service of recreation and skating rink with added value, this will need to create a small business under the administrative guidelines that establish a management model for meeting the objectives. The vision is to achieve in the medium term a level of competitiveness and positioning service with recreation and skating among the main activities of the city of Quevedo. The mission to be a company that provides the service and recreational skating, whose task is to ensure our customers a high quality service through a strategic location, adequate infrastructure, competitive prices and excellent customer service, demonstrating the commitment and our concern for their amusement and recreation to contribute to the national plan for the good life with recreation and tourism development to improve. Fun on wooden track, work on the Ave: Walter Andrade and Canton Guayacán Quevedo, Los Rios Province, which will be relevant conditioning, so it requires a total investment of USD 1,213,445 of which 70% bank credit are $ 849,411, and USD 364 033 are Capital own. Total revenues for the first year is $ 345, 600, net income for the first year is $ 124.484.80, the NPV is $ 1158.472 and IRR is 40.29%, with a positive which means that the project is viable.